Differential Responses of Two Broccoli (Brassica oleracea L. var Italica) Cultivars to Salinity and Nutritional Quality Improvement - Chokri Zaghdoud; Carlos Alcaraz-López; César Mota-Cadenas; María del Carmen Martínez-Ballesta; Diego A. Moreno; Ali Ferchichi; Micaela Carvajal (The Scientific World Journal)
The comparative responses of two broccoli cultivars (Brassica oleracea var. Italica, cv. Parthenon and cv. Naxos) to a 15 d exposure to different NaCl levels were investigated. Salinity led to increased concentrations of Na+ and Cl− ions in both cultivars, a disruption of the endogenous minerals levels in the shoots and roots—that varied with the cultivar and salt concentration—and decreases in the osmotic potential (Ψπ), root hydraulic conductance (L0), and stomatal conductance (Gs). The reduced biomass of Naxos at moderate NaCl indicates greater sensitivity to salinity, compared with Parthenon. Parthenon accumulated more soluble sugars, for osmotic adjustment, whereas Naxos accumulated proline, which gave the two cultivars differing nutritional characteristics. The total glucosinolates (GSLs) content was not affected by salinity in Parthenon while it decreased significantly in Naxos as a consequence of the decrease in the indole GSL. However, Naxos accumulated more aliphatic GSLs under salt stress than Parthenon, which confers on this cultivar a greater nutritional value when cultivated under salinity.These results suggest that, at distinct salinity levels, each broccoli cultivar adopts a specific strategy, indicating the crucial role of the genetic background on the organoleptic and nutritional properties that each cultivar acquires.